Superconducting platinum silicide for electron cooling in silicon. (January 2015) - Prest, M.J.; Richardson-Bullock, J.S.; Zhao, Q.T.; Muhonen, J.T.; Gunnarsson, D.; Prunnila, M.; Shah, V.A.; Whall, T.E.; Parker, E.H.C.; Leadley, D.R.
Highlights: We use platinum silicide as a superconductor contact for electron cooling in silicon. The TC of PtSi is reduced from 1 K to 0.79 K using a thin film (10 nm) of PtSi. The device I – V characteristics are simulated using a tunnelling model. Electron cooling is from 100 mK to 50 mK is deduced from fitting I – V data to a model. The model shows that the thin layer, and reduced TC, is beneficial for cooling. Abstract: We demonstrate electron cooling in silicon using platinum silicide as a superconductor contact to selectively remove the highest energy electrons. The superconducting critical temperature of bulk PtSi is reduced from around 1 K to 0.79 K by using a thin film (10 nm) of PtSi, which enhances cooling performance at lower temperatures. We use an electron cooling model to infer that electrons in silicon are cooled from 100 mK to 50 mK in such a device.